PASTISIPASI SOSIOLOGIS GENERASI Z KRISTIANI DALAM PENINGKATAN KERUKUNAN ANTAR UMAT BERAGAMA DI KOTA BATAM - Gomgom Purba (UPPM Sekolah Tinggi Teologi Tabgha Batam, 2022)
Talking about religious harmony is an important basis in building diversity that must be maintained by generations of a nation. This article offers sociological participation as a new approach for Generation Z in building and preserving religious harmony in Batam City. This approach provides an understanding as well as demonstrates the tasks and challenges for Generation Z Christians that the sociological participation approach provides an impetus to explore roles in pluralism. By conducting a case study by surveying the sociological participation of Generation Z Christians and their implications for inter-religious harmony, the author shows that new social integration can be built. Adaptation of sociological locality and Generation Z Safari in increasing inter-religious harmony in Batam city plays a relevant function in complementing the context, each of which has its own characteristics. In this case, generation Z Christians in the city of Batam are able to become figures who can spread the value of the teachings of Jesus Christ and can be an open letter of God's reconciliation that can be followed in the goodness of living together.